Perancangan Mesin Grinder Coffee Brewer Berbasis Photovoltaic - Laksono, Dyson Rozak; Basri, Muhammad Hasan; Herlina, Amalia; Hasan, Fuad (Universitas Trunojoyo Madura, 2021)
Coffee drinks are in demand by almost all groups of people. In this modern era, along with the high level of people's busyness in activities, so they will be very busy and most of them take a short break to enjoy a cup of coffee as a reliever of drowsiness and an increase in enthusiasm. By designing a photovoltaic-based coffee brewer grinder machine to produce a coffee maker that is suitable for consumption by maintaining a water temperature of 70 oC, so as to produce coffee that is cloudy, light, watery, dark dilute, dark dilute, and dark thick, which is ready to be served for coffee connoisseurs. At the design stage of the on-off temperature control system diagram on the automatic coffee brewer machine heater, the process of making a functional block diagram is carried out. The heating control system on the coffee brewer uses a closed loop control system with feedback using the DHT11 sensor.